2015
DOI: 10.1055/s-0034-1380403
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Trimethylsilyl Chloride Mediated Synthesis of 2,3,5-Trisubstituted Pyrrole Diesters from Nitriles and Ethyl Bromoacetate

Abstract: BrCH 2 COOEt (3 equiv) Zn (2 equiv) TMSCl (0.5 equiv) THF, reflux N H R EtO 2 C CO 2 Et 15 examples upto 91% yield R-CN R = aryl, heteroaryl alkyl, benzyl Abstract An efficient, zinc-mediated, single-pot and CN+3C type pseudo-four-component synthesis of 2,3,5-trisubstituted pyrrole diesters was achieved from readily available aromatic/benzylic/aliphatic nitriles and ethyl bromoacetate under trimethylsilyl chloride catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Rao has shown that aliphatic, aromatic, and benzylic nitriles could be converted into 2,3,5-trisubstituted pyrrole diesters 164 via a zinc-mediated pseudo four-component reaction catalyzed by TMSCl (Scheme 18). 76 The reaction proceeds by the addition of the zinc enolate of ethyl bromoacetate 165 to the nitrile to form enamino ester 166. Then, C-alkylation with another molecule of ethyl bromoacetate produces diester 167, which undergoes Perkin ester condensation with another molecule of zinc enolate 165 to form key intermediate 168; subsequent dehydrative cyclization results in trisubstituted pyrroles 164.…”
Section: Scheme 18 From Cyanidesmentioning
confidence: 99%
“…Rao has shown that aliphatic, aromatic, and benzylic nitriles could be converted into 2,3,5-trisubstituted pyrrole diesters 164 via a zinc-mediated pseudo four-component reaction catalyzed by TMSCl (Scheme 18). 76 The reaction proceeds by the addition of the zinc enolate of ethyl bromoacetate 165 to the nitrile to form enamino ester 166. Then, C-alkylation with another molecule of ethyl bromoacetate produces diester 167, which undergoes Perkin ester condensation with another molecule of zinc enolate 165 to form key intermediate 168; subsequent dehydrative cyclization results in trisubstituted pyrroles 164.…”
Section: Scheme 18 From Cyanidesmentioning
confidence: 99%
“…181 A Blaise-type reaction gave a trisubstituted pyrrole as a byproduct, and the reaction was then optimized to give the trisubstituted pyrrole in 78% yield; the proposed reaction intermediates are shown in Scheme 35. 182…”
Section: Review Syn Thesis 5 the Blaise Reactionmentioning
confidence: 99%